Biology and thermal requirements of Catolaccus grandis (Burks) (Hymenoptera:Pteromalidae) parasitoid of cotton boll weevil - Wanderley, Paulo A.; Ramalho, Francisco S. (Pesquisa Agropecuaria Brasileira, 1996)
The biology and thermal requirements of Catolaccus grandis (Burks) (Hymenoptera:Pteromalidae) a parasitoid of cotton boll weevil, Anthonomus grandis Boheman were studied at constant temperatures of 18; 20; 23; 25; 28; 30; 35 and 38°C, relative humidity of 60 ± 10% and a 14L:10D photoperiod. The development time from egg to adult emergence of males was of 8.61 to 26.48 days and for females was of 9.44 to 31.40 days, in function of the temperature in which the parasitoid was maintained. Parasitoid eggs desiccate and fail to hatch at 38°C. Lower developmental threshold temperatures and thermal constants for development of C. grandis vary with the instar, immature stages, and sex.